Ar-CO-liquid steel flow with decarburization chemical reaction in single snorkel refining furnace. (January 2020) - Chen, Shifu; Lei, Hong; Wang, Meng; Yang, Bin; Dou, Weixue; Chang, Lishan; Zhang, Hongwei
Highlights: A two-way coupling mathematical model is proposed to investigate the multiphase flow, mass transfer and chemical reaction. The CO generation rate is greater than argon blowing rate at the first 12 minutes of decarburization. The stirring effect of CO gas can enhance the carbon and oxygen mass transfer and promote the decarburization rate. Abstract: As a new style refining equipment developed from the traditional RH furnace, Single Snorkel Refining Furnace (SSRF), which is also called as single snorkel RH, is widely used for producing ultra-low carbon steel. However, the effect of CO gas on fluid flow and decarburization is not reported in the existing literatures. Based on the Eulerian-Eulerian approach, a two-way coupling mathematical model considering CO gas is proposed to investigate the coupling phenomenon of Ar-CO-liquid steel flow and decarburization in SSRF. And the industrial experimental data is employed to validate the numerical result. In comparison with the one-way coupling model, the numerical result predicted by the two-way coupling model is closer to the industrial experimental data. The CO mole number, which is generated by the overall decarburization process, is about 3 times the argon mole number blown into the ladle, and the CO generation rate is greater than argon blowing rate at the first 12 min. Because of the stirring effect of CO gas, there are the more complex fluid flow, the stronger mass transfer, the greater decarburization rate and the lower carbon mass concentration in the liquid steel during decarburization. Besides, the Ar plume area predicted by the two-way coupling model is larger and it is closer to the center line of the snorkel. Therefore, the effect of CO gas on the fluid flow cannot be ignored and the two-way coupling model can describe the metallurgical phenomena in SSRF more precisely.